Tillförsel av använda fosforfilter påverkar inte tillväxten eller fosforupptaget hos korn - Tylstedt, Emma (SLU/Dept. of Crop Production Ecology, 2012)
The eutrophication of inshore seas, lakes and watercourses is mainly due to leaching of nitrogen and phosphorus (P) from agriculture. Many efforts are made to reduce the lea-kage of phosphorus in Sweden and the Baltic Sea countries. Phosphorus is also a finite resource and the mining of good quality raw material gets more and more difficult. Se-dimentation dams in combination with filters is one relatively new method to separate P from run-off and drainage water from agricultural land. This study was a part of an IVL Swedish Environmental Research Institute’s project which tests the capacity and func-tion for separation of phosphorus in four phosphorus filters. The main focus in this study was to investigate the phosphorus fertilizing effect of recycled used filter material on barley. Such filters have earlier shown to have a liming effect on soils.